Collaborative dual-arm robot system for aircraft ground refuelling - Tang, Gilbert; Singh, Simrat; Rice, Jamie; Kuang, Boyu; Barnes, Stuart; Jenkins, Karl (Institute of Electrical and Electronics Engineers (IEEE), 2025)
The growing demand for automation, alongside advancements in robotics, sensing, and artificial intelligence, is driving the adoption of professional service robots across multiple sectors. In the aerospace industry, aircraft ground refuelling remains a hazardous, labour-intensive task with significant potential for robotic automation. Despite decades of interest, autonomous refuelling has yet to be realised due to the complexity of the environment, technical challenges in nozzle manipulation, and limitations of legacy robotic systems. This paper presents a novel collaborative closed-loop kinematic chain robot for autonomous fuel nozzle positioning and latching. The system addresses key challenges such as accurate fuel port localisation, precise nozzle manipulation and positioning, and secure connection, all within a semi-structured airport environment. A robot demonstrator was developed as part of an industry-funded project aimed to demonstrate the solution’s potential to enhance safety and improve efficiency in commercial aircraft refuelling.
Keywords: 40 Engineering; 4001 Aerospace Engineering; 46 Information and Computing Sciences; 4007 Control Engineering, Mechatronics and Robotics; 4602 Artificial Intelligence; 9 Industry, Innovation and Infrastructure; Aviation MRO; autonomous manufacturing; robotics; aircraft refuelling; close-loop kinematic chain; dual-arm robot